(untitled) (Sebha University Conference Proceedings, 2024)
The main goal of this study (which the comprehensive reservoir study for Libyan X Field plan of development) is to predict future performance of a reservoir and find ways and means of optimizing the recovery of some of the hydrocarbon under various operating conditions. The simulator results show the reservoir pressure history curve is matching to the stimulation curve, this gives a good indication of the input data that has been entered to the model. The driving mechanism for all those reservoirs it comes from three natural forces, which are fluid expansion, PV compressibility, and water influx. The best method to choose as secondary recovery for this oil field is water and gas Injection. Water and gas Injection have the largest Total Field Recovery. Water and gas Injection have the highest Reservoir Pressure at the end of the project. The highest percentage of oil recovery was when the water and gas were injected and it reached 58%, then when the water was injected and it reached 55%, and then when the gas was actually injected and it reached 54%. The field pressure rise was greater when water and gas were injected, and the pressure reached 792 psi, while it was less when only water was injected, reaching 435.5 psi, and when only gas was injected, it reached 412.9 psi. Finally, central objective of this master thesis with the help of reservoir simulation fulfilled to produce future prediction that will lead to optimize reservoir performance which meant reservoir developed in the manner that brings utmost benefit to the commercial business.